The Antimicrobial Properties of Selected Oils Used as Cosmetics Compounds - Marchwińska, Katarzyna; Michocka, Katarzyna (Studia Oeconomica Posnaniensia, 2017)
Cosmetic vegetable oils for centuries have been objects of interest as ingredients of natural personal care products. Nowadays the trend for coming back to nature has caused their increased popularity in the preparation of natural cosmetics, soaps, and fragrance oils. The aim of the study was to evaluate the antimicrobial properties of 18 selected cold pressed cosmetic oils towards human pathogens. The antagonistic activity of cosmetic oils was assayed by the disc diffusion method. Indicator microorganisms chosen for the study were the bacteria Staphylococcus epidermidis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and yeasts Candida albicans. The conducted research showed that selected cosmetic oils demonstrate different anta-gonistic effects towards indicator microorganisms. The highest antibacterial activity was found in tamanu seed oil. This cosmetic oil decreased the growth of S. aureus, S. epidermidis and P. aeruginosa to a significant level. Wheat germ oil inhibited the growth of S. epidermidis and P. aeruginosa. The oil of the black cumin seed was showed antibacterial activity towards S. aureus. None of the other tested cosmetics oils exhi-bited antimicrobial activity towards selected microorganisms as well as none of them was effective enough to inhibit the growth of E. coli and C. albicans. The antibacterial properties of the selected oils depended on their type as well as tested microorganism.